2010
DOI: 10.1007/s10528-010-9392-6
|View full text |Cite
|
Sign up to set email alerts
|

Defining a New Candidate Gene for Amelogenesis Imperfecta: From Molecular Genetics to Biochemistry

Abstract: Amelogenesis imperfecta is a group of genetic conditions that affect the structure and clinical appearance of tooth enamel. The types (hypoplastic, hypocalcified, and hypomature) are correlated with defects in different stages of the process of enamel synthesis. Autosomal dominant, recessive, and X-linked types have been previously described. These disorders are considered clinically and genetically heterogeneous in etiology, involving a variety of genes, such as AMELX, ENAM, DLX3, FAM83H, MMP-20, KLK4, and WD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 72 publications
(117 reference statements)
0
38
0
4
Order By: Relevance
“…In humans, the hypomineralization or hypoplastic classes of amelogenesis imperfecta have been related to mutations in the following genes: AMELX (Hart et al 2002;Kim et al 2004;Stephanopoulos et al 2005;Urzúa et al 2011), ENAM (Hart et al 2003;Hu and Yamakoshi 2003;Kim et al 2005;Stephanopoulos et al 2005), and recently AMBN (Poulter et al 2014). The mouse model in which exons 5 and 6 are deleted from Ambn showed severe hypoplastic amelogenesis imperfecta that had no enamel formation on the tooth surface (Fukumoto et al the genuine casein kinase phosphorylating secretory calcium-binding phosphoproteins (Ishikawa et al 2012;Tagliabracci et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the hypomineralization or hypoplastic classes of amelogenesis imperfecta have been related to mutations in the following genes: AMELX (Hart et al 2002;Kim et al 2004;Stephanopoulos et al 2005;Urzúa et al 2011), ENAM (Hart et al 2003;Hu and Yamakoshi 2003;Kim et al 2005;Stephanopoulos et al 2005), and recently AMBN (Poulter et al 2014). The mouse model in which exons 5 and 6 are deleted from Ambn showed severe hypoplastic amelogenesis imperfecta that had no enamel formation on the tooth surface (Fukumoto et al the genuine casein kinase phosphorylating secretory calcium-binding phosphoproteins (Ishikawa et al 2012;Tagliabracci et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Prediction tools indicated that the target genes of miR-224 include genes encoding a set of crucial ion transporters required for the development of normal enamel, including SLC4A4 and CFTR (5,6,41). NBCe1 (encoded by SLC4A4), AE2 (encoded by SLC4A2), and CFTR (encoded by CFTR) have been proposed to compose a buffering system during ameloblast differentiation and enamel mineralization (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…: amelogenin (AMELX), enamelin (ENAM), kallikrein-4 (KLK-4), matrix metalloprotease-20 (MMP-20), ameloblastin 3 and more recently DLX3, 4 FAM83H, 5,6,7 WDR72 5 and SLC4A4. 8 AMELX encodes a member of the amelogenin family of extracellular matrix protein and has an important role in biomineralization during tooth enamel development. 9 The X-linked amelogenin gene is located on the Xp22.31-…”
Section: 2mentioning
confidence: 99%